BDNF as a potential biomarker for the fibromyalgia-like model in male wistar rats - Silva de Souza, Vanessa; Fernandes Medeiros, Liciane; Stein, Dirson João; Lino de Oliveira, Camila; Richardt Medeiros, Helouise; Dussan-Sarria, Jairo; Torres, Iraci Lucena da Silva; Souza, Andressa (Clinical and Biomedical Research, 2024)
Introduction: Fibromyalgia syndrome is characterized by central sensitization, with imbalance between the descending pain inhibition pathways and the ascending pain signaling pathways, including changes in the serotonergic, dopaminergic and catecholaminergic circuits. The aim was to evaluate the nociceptive response, depression-like behavior, and central and peripheral biomarkers levels (BDNF and TNF-ɑ) in male adult Wistar rats submitted to a fibromyalgia-like model induced by reserpine. Methods: Sixteen male adult Wistar rats were allocated by weight in control and fibromyalgia groups. Mechanical and thermal hyperalgesia were evaluated by Von Frey test and Hot Plate test respectively, and depression-like behavior was evaluated by Forced Swim test. Also BDNF and TNF-ɑ were measured in serum and central structures. Results: Rats in the fibromyalgia group presented a lower thermal and mechanical threshold, and an increased immobility time. also reduced serum BDNF levels, without changes in TNF-ɑ levels. There was a positive correlation between mechanical and thermal nociceptive threshold and serum BDNF levels, and a negative correlation between thermal nociceptive threshold and spinal cord BDNF levels. Also, there was a negative correlation between immobility time and serum BDNF levels. Conclusion: In summary, this study provides confirmation that the fibromyalgia-like model induced by reserpine effectively replicates the symptoms of fibromyalgia. Additionally, it provides evidence supporting the involvement of brain-derived neurotrophic factor (BDNF) in the development of this pain model.